The splendor of ethnic jewelry from the Colette and Jean-Pierre Ghysels Collection - Taylor, John Bigelow 1950- (Abrams, 1994)
Among the world's finest private collections of ethnic jewelry is that of Colette and Jean-Pierre Ghysels. Formed over the course of more than thirty years of dedicated world travel, conscientious trekking, and trading, the Ghysels' collection has, until now, not been available for viewing except to the couple's friends and selected scholars. Never exhibited extensively, never published in any comprehensive way, the collection has remained carefully protected in Brussels
Aus dem Franz. übers.
Keywords: Ghysels, Colette -- Art collections -- Catalogs; Ghysels, Jean-Pierre -- Art collections -- Catalogs; Ethnic jewelry -- Private collections -- Belgium -- Brussels -- Catalogs; Schmuck; Ethnologie; Belgien; Katalog